PEMANFAATAN APLIKASI GOOGLE MEET SEBAGAI MEDIA PEMBELAJARAN PADA MAHASISWA MANAJEMEN PRODUKSI BERITA DI SEKOLAH TINGGI MULTI MEDIA MMTC YOGYAKARTA - Asiatun, Siti (MEDIALOG: Jurnal Ilmu Komunikasi, 2023)
The Covid-19 pandemic that hit Indonesia had an impact on limiting community activities in various fields, including in education. Through a letter on the Implementation of Educational Policies in the Emergency Period for the Spread of Coronavirus Disease (Covid-19), the learning method is regulated remotely or online. Sekolah Tinggi Multi Media MMTC implements this decision by conducting theoretical and practical lectures by utilizing information technology or online. Google Meet application is one of the learning media used by students and lecturers in the news production management study program that has its advantages and disadvantages. This study aims to understand the use of the Google Meet application as a learning medium for news production management students at Sekolah Tinggi Multi Media MMTC. Qualitative method is used for this research with data obtained from direct interviews with representatives of lecturers and students of news production management. Secondary data is obtained through the Broadcasting Law, books, journals, and related articles published on the internet. It can be concluded that the overall features available in the Google Meet application make it easier for respondents to study remotely. However, this is still limited to learning about theory, not practical work.